THE INFLUENCE OF KOREAN CULTURE FANATISM ON LIFESTYLE, THROUGH MEDIATION OF SOCIAL MEDIA USE AT CGV FOCAL POINT MEDAN - Rudi Purnomo; Suryani Hardjo; Patisina (RADJA PUBLIKA, 2023)
The lifestyle of watching Korean films is currently increasingly in demand and even several films starring several K-pop idols from certain boy bands are also in great demand by their fans. Their penchant for Korean culture can form a consumptive lifestyle. This phenomenon is demonstrated by the willingness of fans to pay a sizable amount to rent a studio so they can watch with other fanbase members. The purpose of this study was to find out and analyze the influence of lifestyle on Korean cultural fanaticism through mediating the use of social media at the CGV Focal Point Medan. Researchers use quantitative research methods. The results showed a significant positive influence of Korean cultural fanaticism on the use of social media on CGV Focal Point viewers. There is a significant positive influence on the lifestyle of the CGV Focal Point Medan audience on the use of social media. There is a significant positive influence of Korean culture fanaticism on the lifestyle of CGV Focal Point Medan audience. There is a mediating role in the use of social media in the influence between Korean cultural fanaticism on the lifestyle of the audience at CGV Focal Point Medan.